Choline Autoradiography of Human Prostate Cancer Xenograft: Effect of Castration - Hossein Jadvar; Alparslan Gurbuz; Xiankui Li; Antranik Shahinian; Peter S. Conti (Molecular Imaging)
The purpose of this study was to investigate the effects of castration and tracer uptake time interval on the level of radiolabeled choline accumulation in murine-implanted human prostate tumor xenografts using quantitative autoradiography. We implanted androgen-dependent (CWR22) and androgen-independent (PC3) human prostate cancer cells in castrated ( n = 9) and noncastrated ( n = 9) athymic male mice and allowed tumors to grow to 1 cm 3 . The mice were euthanized at 5, 10, and 20 minutes after injection of 5 µCi [14C]-choline. Mice were prepared for quantitative autoradiography with density light units of viable tumor sections converted to units of radioactivity (nCi/mm 2 ) using calibration. Two-group comparisons were performed using a two-tailed Student t -test with unequal variance and with a significance probability level of less than .05. Two-group comparisons between the means of the tracer uptake level for each tumor type at each of three time points for each of two host types showed that (1) the level of tracer localization in the two tumor types was affected little in relation to the host type and (2) PC3 tumor uptake level tended to increase slowly with time only in the noncastrated host, whereas this was not observed in the castrated host or with CWR22 tumor in either host type. The uptake time interval and castration do not appear to significantly affect the level of radiolabeled choline uptake by the human prostate cancer xenograft.